Generalized D-dimensional lagrangians and early gravitational waves - Amendola, Luca; Litterio, Marco; Occhionero, Franco (Physics letters, 2002)
Following a preceding paper, we extend here the constraints arising from the upper limits on the anisotropy of the microwave background radiation, to models in multidimensional generalized gravitational lagrangian. We underline that the relevant equations can be easily written out if we perform two successive conformal transformations. In the situation in which a flat, inflation driving potential is realized, we show that the spectrum of the gravitational wave perturbations — and hence of the MBR anisotropy — is absolutely flat only when D=4 and depends in general on the inner space compactification.
Gesehen am 22.11.2017